A Plea for Embodied Spirituality: The Role of the Body in Religion By F. Watts (2021). (24th July 2022) - Wallace, Rebekah
Abstract : A Plea for Embodied Spirituality: The Role of the Body in Religion By F. Watts (2021) London: SCM Press, ix + 230pp.